2010
DOI: 10.1088/0022-3727/43/39/395101
|View full text |Cite
|
Sign up to set email alerts
|

Modification of silver anode and cathode for a top-illuminated organic photovoltaic device

Abstract: We have demonstrated a top-illuminated organic photovoltaic device with a thick Ag anode and a thin Ag cathode capped with an α-naphthylphenylbiphenyl diamine (NPB) thin film. The surface of the Ag anode was oxidized by UV–ozone which improved the carrier collection and reduced the exciton quenching. Compared with the control device with an indium tin oxide anode, a 15.59 times reduction in the serial resistance and a 1.72 times increase in the shunt resistance were observed with a fill factor of 0.61 in such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…While aluminium is a common cathode in conventional device designs, inverted device designs typically use a silver cathode. Although silver also oxidises, oxides of silver are electrically conductive and have even been used as interfacial layers to improve performance in OPV devices [31,32]. Despite the absence of severe degradation, we have found that LBIC measurements can still be used to track the ingress of water in devices with a silver cathode.…”
Section: Ingress In Devices With a Silver Cathodementioning
confidence: 90%
“…While aluminium is a common cathode in conventional device designs, inverted device designs typically use a silver cathode. Although silver also oxidises, oxides of silver are electrically conductive and have even been used as interfacial layers to improve performance in OPV devices [31,32]. Despite the absence of severe degradation, we have found that LBIC measurements can still be used to track the ingress of water in devices with a silver cathode.…”
Section: Ingress In Devices With a Silver Cathodementioning
confidence: 90%
“…10 nm Ag film possesses a higher average transmittance. A severe transmittance dip happened at 430 nm may be resulted from the enhanced scattering of Ag clusters under plasmonic resonance, which implied the film formation is discontinuous [22]. Corresponding to its I-V curve in inset of Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Thin Ag film was reported to be transparent electrode due to its good conductivity and high transmittance in visible band [18,22]. However, it is a challenge to form a stable, continuous, conductive and transparent thin Ag film.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous reports [24,25], we used Ag film as the anode and cathode to obtain an efficient top-illuminated organic photovoltaic (TOPV) device. However, many studies indicated that metal-induced exciton quenching degrades the number of excitons by nonradiative energy transfer to the metal [26][27][28].…”
Section: Introductionmentioning
confidence: 99%